Pemeriksaan EHP dan AHPND pada Litopenaeus vannamei dengan Metode PCR di BKHIT Jawa Timur - Maria Agustina Pardede; Silvani Tri Julianti; Putri Puspita Sari; Hesti Listiyani; Dewi Kartika; Siti Mufidah; Muhammad Adrian Fauzi; Mohamad Fathoni (Jurnal Pendidikan Kimia, Fisika dan Biologi, 2025)
White shrimp (Litopenaeus vannamei) is an introduced species cultivated in Indonesia and plays an important role in increasing national shrimp production and exports. However, infectious diseases such as Enterocytozoon hepatopenaei (EHP) and Acute Hepatopancreatic Necrosis Disease (AHPND) pose a serious threat to the shrimp farming industry. These two diseases cause a decrease in shrimp growth and production performance. The Polymerase Chain Reaction (PCR) diagnostic technique is an effective method for detecting EHP and AHPND infections, because the results are fast and accurate. This research was carried out at the Juanda Fish Quarantine Laboratory, Animal, Fish and Plant Quarantine Center (BKHIT) East Java from July 1 to August 29 2024. This research aims to find out examination techniques and examination results for Enterocytozoon hepatopenaei (EHP) and Acute Hepatopancreatic Necrosis Disease (AHPND) during the examination process at BKHIT East Java. The test method used is a descriptive method by collecting primary and secondary data. The EHP examination at BKHIT East Java uses the single step PCR method, while the AHPND examination uses the Nested PCR method which consists of extraction, amplification, electrophoresis and visualization of the results. Based on the results of examinations during the activity, 4 samples were declared positive for EHP and no samples were declared positive for AHPND out of 51 samples of white shrimp (Litopenaeus vannamei).